Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1990
DOI: 10.1115/90-gt-009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Mainstream Turbulence on Leading Edge Film Cooling Heat Transfer

Abstract: The influence of high mainstream turbulence on leading edge film effectiveness and heat transfer coefficient was studied. High mainstream turbulence was produced by a passive grid and a jet grid. Experiments were performed using a blunt body with a semi-cylinder leading edge with a flat afterbody. The mainstream Reynolds number based on leading edge diameter was about 100,000. Spanwise and streamwise distributions of film effectiveness and heat transfer in the leading edge and on the flat sidewall were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…Following this work, Ou et al [9] experimentally determined the effect of the film hole row location on the leading edge film cooling under high mainstream turbulence conditions (Tu = 9.67%). Two locations of film injection cooling holes, located only at ±15°or ±40°, were studied and compared to the four-row configuration reported by Mehendale and Han [8]. The results showed that the mainstream turbulence effect was more severe for the ±15°one-row injection than for the ±40°one-row injection.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Following this work, Ou et al [9] experimentally determined the effect of the film hole row location on the leading edge film cooling under high mainstream turbulence conditions (Tu = 9.67%). Two locations of film injection cooling holes, located only at ±15°or ±40°, were studied and compared to the four-row configuration reported by Mehendale and Han [8]. The results showed that the mainstream turbulence effect was more severe for the ±15°one-row injection than for the ±40°one-row injection.…”
Section: Introductionmentioning
confidence: 94%
“…Tests were performed using a blunt body with a cylindrical leading edge and a flat afterbody. Adopting the same leading edge model, Mehendale and Han [8] studied the effects of the blowing ratio (from G = 0.4 to 1.2) and the free-stream turbulence intensity (Tu = 0.75%, 9.67%, 12.9%) downstream of two staggered rows of holes located at ±15°and ±40°from the stagnation line. Following this work, Ou et al [9] experimentally determined the effect of the film hole row location on the leading edge film cooling under high mainstream turbulence conditions (Tu = 9.67%).…”
Section: Introductionmentioning
confidence: 99%
“…Downstream of the cooling jets, the spanwise average of mass transfer was found to be increased by a factor of two over that without film cooling at a blowing ratio of M = 2, and the size of the elevated mass transfer region was observed to increase with the blowing ratio. Mehendale and Han (1992) On the stagnation line, the heat transfer coefficient was found to be increased by 80% for a blowing ratio M = 1.9. Downstream of the off-stagnation holes, the heat transfer coefficient was more than doubled.…”
Section: Experimental Study Of the Heat Transfer Coefficient Augmentamentioning
confidence: 98%
“…Oldfield (1992, 1996) and the previous work by Holmberg (1996) and Holmberg and Pestian (1996) are the exceptions. Giel, et al (2000) Low speed 0.11 18% Barringer, et al (2002) Low speed 0.43 18% Wang, et al (1998) Low speed -20% Thole, et al (1994) Low speed 0.11 13% Low speed -10% Boyle, et al (1998) Low speed -17% Schauer and Pestian (1996) Low speed -20% Radomsky and Thole (2000) Transonic <0.1 5% Holmberg (1996) Low speed -13% Mehendale and Han (1992) …”
Section: Time-resolved Heat Transfermentioning
confidence: 99%